Chromic Properties of Carboxyphenyl Viologen Induced by Complexation in Cucurbit[7]uril. Issue 7 (16th February 2021) - Luo, Dan; Guang, Long‐Yu; Lin, Rong‐Guang; Zhang, Ning‐Ning; Liu, Mei‐Chen; Lin, Rui‐Lian; Sun, Wen‐Qi; Liu, Jing‐Xin
Abstract: Upon encapsulation in cucurbit[7]uril, carboxyphenyl viologen exhibited dramatically enhanced photochromism, while its alkaline form exhibited enhanced thermochromism. ESR experiments and reorientation energy calculation indicate that these chromic behaviors are caused by the electron transfer from the host to the guest. Abstract : Upon encapsulation in cucurbit[7]uril, the carboxyphenyl viologen and its alkaline form exhibited fast responsive photochromic and thermochromic properties respectively, which are caused by the electron transfer from the host to the guest.